2015
DOI: 10.1002/pc.23869
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanoparticles on the morphology and properties of PET/PP in situ microfibrillar reinforced composites

Abstract: In this work, the effect of SiO2 nanoparticles on the morphology and properties of PET/PP in situ microfibrillar reinforced composites (MFC) obtained from slit die extrusion and hot stretching‐quenching was investigated. The scanning electron micrographs revealed that the nanoparticles could have different effects on microfibril formation of PET/PP MFC depending on their concentration. Addition of appropriate content of nanoparticles (e.g., 1.6 and 8 wt%) facilitated the PET droplet‐fibril transition during st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
(36 reference statements)
1
6
0
Order By: Relevance
“…Since melting temperature of PP and glass transition temperature of PET comes near each other at around 80 °C, this region is analyzed for thermal characterization of fabricated systems. Similarly, merging of melting temperature and glass transition temperature of two different polymer has also been previously reported [ 7 ]. In the present case there is no peak in DSC thermogram instead of melting region 145–155 °C.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Since melting temperature of PP and glass transition temperature of PET comes near each other at around 80 °C, this region is analyzed for thermal characterization of fabricated systems. Similarly, merging of melting temperature and glass transition temperature of two different polymer has also been previously reported [ 7 ]. In the present case there is no peak in DSC thermogram instead of melting region 145–155 °C.…”
Section: Resultssupporting
confidence: 67%
“…Recently, PP has been blended with some high-melting-point polymers such as PET, Nylon, Ethylene Vinyl Acetate Copolymer (EVA), etc. using different kinds of nanofillers as discussed elsewhere to increase miscibility and to minimize phase separation [ 7 , 8 ]. The main nanofillers presently used to reinforce the properties of blend nanocomposites are graphene, graphene oxide, and single/few-layer Boron Nitride (BN) [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Liu and co‐workers [ 211 ] have prepared MFCs with silica nanoparticles via hot stretching and achieved very interesting results. The elasticity of the blend was enhanced by incorporating the nanoparticles during the melt mixing, making it easier for the PET to deform.…”
Section: Processing–structure–property Relationship Of Microfibrillarmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] That can be attributed to the following aspects. [8][9][10][11][12][13][14] That can be attributed to the following aspects.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] That can be attributed to the following aspects. 10,14 On the other hand, the introduction of nanoparticles into blends as compatibilizers to control the morphology structure of blends has also been widely reported. Mdletshe et al 12 found that adding silicon carbide nanoparticles into PCL would increase cooling crystallization temperature (T c ), implying that nanoparticles have nucleating effects.…”
Section: Introductionmentioning
confidence: 99%